Application of Electrode Methods in Studies of Nitric Oxide Metabolism and Diffusion Kinetics - Liu, Xiaoping (2012)
Nitric oxide (NO) has many important physiological roles in the body. Since NO electrodes can directly measure NO concentration in the nM range and in real time, NO electrode methods have been generally used in laboratories for measuring NO concentration in vivo and in vitro. This review focuses on the application of electrode methods in studies of NO diffusion and metabolic kinetics. We have described the physical and chemical properties that need to be considered in the preparation of NO stock solution, discussed the effect of several interfering factors on the measured curves of NO concentration that need to be eliminated in the experimental setup for NO measurements, and provided an overview of the application of NO electrode methods in measuring NO diffusion and metabolic kinetics in solution and in biological systems. This overview covers NO metabolism by oxygen (O(2)), superoxide, heme proteins, cells and tissues. Important conclusions and physiological implication of these studies are discussed.